The Rise of the South human progress in a diverse world - Malid, Khalik; UNDP (New York UNDP, 2013)
The 2013 Human Development Report ? "The Rise of the South: Human Progress in a Diverse World" ? examines the profound shift in global dynamics driven by the fast-rising new powers of the developing world and its long-term implications for human development. The Report identifies more than 40 countries in the developing world that have done better than had been expected in human development terms in recent decades, with their progress accelerating markedly over the past ten years. The Report analyzes the causes and consequences of these countries' achievements and the challenges that they face today and in the coming decades. Each of these countries has its own unique history and has chosen its own distinct development pathway. Yet they share important characteristics and face many of the same challenges. They are also increasingly interconnected and interdependent. The Report calls for far better representation of the South in global governance systems and points to potential new sources of financing within the South for essential public goods. With fresh analytical insights and clear proposals for policy reforms, the Report helps charts a course for people in all regions to face shared human development challenges together, fairly and effectively.
Keywords: Human Devepment, Governance